Clochan Dwellings
A number of late examples of primitive dry stone huts, called Clochan in Ireland have survived in the Dingle peninsular and are among the earliest complete remains of dwelling places in the British Isles. They were built by anchorite monks, who required the minimum of basic necessities, and are a reflection of the houses built by later Iron Age people. Yet they surely have more than a geometric similarity with hut circle remains and can be seen as an archetypal house. Projecting corbels allow a layer of turf to be applied for weathering. The doorway of the foremost hut is modern.